From Plant to Chemistry: Sources of Antinociceptive Non-Opioid Active Principles for Medicinal Chemistry and Drug Design - Rita Turnaturi; Silvia Piana; Salvatore Spoto; Giuliana Costanzo; Lorena Reina; Lorella Pasquinucci; Carmela Parenti (Molecules, 2024)
Pain is associated with many health problems and a reduced quality of life and has been a common reason for seeking medical attention. Several therapeutics are available on the market, although side effects, physical dependence, and abuse limit their use. As the process of pain transmission and modulation is regulated by different peripheral and central mechanisms and neurotransmitters, medicinal chemistry continues to study novel ligands and innovative approaches. Among them, natural products are known to be a rich source of lead compounds for drug discovery due to their chemical structural variety and different analgesic mechanisms. Numerous studies suggested that some chemicals from medicinal plants could be alternative options for pain relief and management. Previously, we conducted a literature search aimed at identifying natural products interacting either directly or indirectly with opioid receptors. In this review, instead, we have made an excursus including active ingredients derived from plants whose mechanism of action appears from the literature to be other than the modulation of the opioid system. These substances could, either by themselves or through synthetic and/or semi-synthetic derivatives, be investigated in order to improve their pharmacokinetic characteristics and could represent a valid alternative to the opioid approach to pain therapy. They could also be the basis for the study of new mechanisms of action in the approach to this complex and disabling pathology.